AN ANALYSIS ON STUDENTS’ GRAMMATICAL ERRORS IN PERFORMING ENGLISH STORYTELLING - Ibnu Kamil Antakusuma (Vidya Karya, 2019)
Abstract. This research aimed to identify, and in advance, to analyze the subject of analysis of the research during the performances of the students in English storytelling. Total of the students that acted as the research population were 44 students of SMA Negeri 1 Banjarmasin. There was a specially designed observation sheet used as the main tool or research instrument to retrieving the data. As the result, there were 37 errors happened during the students’ performances. The errors then classified into 4 categories in the taxonomy of surface structure. Keywords: errors, grammatical, storytelling, speaking, surface strategy taxonomy, error analysis